Problemy organizatsii nachal'nogo obucheniya plavaniyu detei-invalidov - Mosunov, D. F. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to reveal the problems of organization and realization when primary instructing of disabled children in swimming. The natural pedagogical experiment and pedagogical observations with a help of the underwater and surface shooting had been used as the methods of this research. The next main problems of disabled children's instructing in swmming had been revealed as a result of the study.